COMMUNITY BASED SUSTAINABLE TOURISM DEVELOPMENT IN THE DISTRICT OF EAST SUMBA - Gunawan, Fransiskus Xaverius Candra (Journal Economics & Business Atmajaya Indonesia, 2020)
It is undeniable that the writhing of tourism in East Sumba is the impact of electronic and digital media coverage of the determination of Nihiwatu beach as one of the most beautiful beaches in the world. As a newly developed tourist area this phenomenon is a momentum for the people's economic revival that must be immediately and accurately addressed by the Regional Government. This study aims to analyze the development of community-based sustainable tourism in Walakiri beach tourism objects located in Watumbaka Village, Pandawai sub District with aspects of the research of the role of the Regional Government and the economic impacts that occur at the Community level. The data analysis technique used is qualitative descriptive analysis and SWOT (strenghts, weaknesess, opportunity, and threat). The data used are secondary and primary data obtained by observation and interviews. Until now, Local Governments have not fully been able to implement sustainable tourism development programs due to the status of land ownership of some communities including commensurate beaches which hamper the tourism development spatial planning process. Therefore, the Regional Government and the Community need to design the concept of Sustainable Tourism Development which can accommodate the interests of all parties. The implementation of the Community Based Tourism (CBT) approach model can be an option for the sustainable tourism development approach that will be implemented.